Determination of copper, iron, nickel and zinc in gasoline by FAAS after sorption and preconcentration on silica modified with 2-aminotiazole groups - Roldan, P. S.; Alcantara, I. L.; Padilha, CCF; Padilha, P. M. (Elsevier B.V., 2005)
Silica gel chemically modified with 2-aminotiazole groups (SiAT), was used for preconcentration of cupper, zinc, nickel and iron from gasoline, normally used as a engine fuel. Surface characteristics and surface area of the silica gel were obtained before and after chemical modification using FT-IR, Kjeldhal and surface area analysis (B.E.T.). The retention and recovery of the analyte elements were studied by applying batch and column techniques. The experimental parameters, such as shaking time in batch technique, flow rate and concentration of the eluent (HCl-0.25-2.00 mol 1(-1)) and the amount of silica, on retention and elution, have been investigated. Detection limits of the method for cupper, iron, nickel and zinc are 0.8, 3, 2 and 0.1 mug 1(-1), respectively. The sorption-desorption of the studied metal ions made possible the development of a preconcentration method for metal ions at trace level in gasoline using flame AAS for their quantification. (C) 2004 Published by Elsevier Ltd.
Keywords: preconcentration; metal ions; gasoline; FAAS determinations